(untitled) (Fiep Bulletin - online, 2014)
Many of the successful athletes in the main international competitions are the result of systems of detection, selection and promotion of sports talents (DSPTE). The creation of unified and efficient systems of DSPTE based on technical and scientific criteria can be considered sine qua non in the process of long term formation of young athletes on their way to high performance in countries with excellence in sports. Even though Brazil is part of the four best placed Iberian-American countries in the ranking of athletics, along with Cuba, Portugal and Spain, it has not yet developed a unified national system for the modality and is beginning to implant a system for the sport in general. For that reason, our objectives are: (1) To describe the existing national programs for athletics in each Iberian-American country; (2) To analyse these programs according to the elements that compose them; (3) To compare the Brazilian program with the other Iberian-American countries of our sample; and (4) To offer suggestions that could be useful for the development of a Brazilian system of DSPTE for athletics. Our conclusions and recommendations for the implanting of a Brazilian system of DSPTE for athletics are: (1) To create a department for DSPTE within the CBAt and its state subdivisions; (2) To develop a program of DSPTE with its own mechanisms (creation of athletics schools, specific processes for talent selection and programs for the promotion of the athletes); (3) To improve and increase the infrastructures (tracks, training and promotion centres); (4) To captivate and instruct a greater number of coaches and monitors; and (5) To offer more support to the athletes (financial, material and multidisciplinary).